A clínica psicanalítica no hospital: a elaboração do sofrimento psíquico a partir da angústia em pacientes oncológicos - SOUZA, Elaine Antunes de (Universidade Federal do Pará, 2025)
This present work will address the dimension of the psychoanalytic clinic in the hospital, considering the psychic elaboration of suffering in subjects who are overcome by anguish when facing an oncological diagnosis. In the context of oncological treatment, we find the social representation of the disease associated with death, still considered a taboo topic. This social imaginary has very ancient roots in history, being marked by intense physical and psychological suffering, since the disease was often accompanied by death, regardless of the treatment carried out. When it comes to illness due to cancer, the exercise of psychoanalysis in the hospital takes place on an urgent basis, or better said, subjective urgency, in which we seek to understand the psychic repercussions, which are shaken at this moment of illness. The idea of subjective urgency refers to the breaking of the subject's speech when faced with something unbearable, without symbolic mediation. At this moment, lacking words to name this situation, the ill subject positions his psychic reality in action. Suffering manifested through human relationships and the finiteness of one's own body presents itself in an imperious way, as it links suffering to what is ineluctable and escapes the subject's full control. And the body, as it is part of nature, imposes limits in relation to its functioning and duration, which in this case, we can consider the experience of psychological suffering in cancer, being manifested in the body. To understand anguish, which from the beginning became central in psychoanalytic theory, Freud came across this concept in the clinic of neuroses, starting to investigate its forms of psychic manifestations, developing his theory addressing this important concept. In his Draft It is considered one of the most important writings addressed to Fliess, on the affect of anxiety, which associates it with another central concept in psychoanalytic theory, sexuality. We can observe that Freud writes about two theories, the first mentioned as being a transformation of libido and the second, the theory of repression. For Lacan, anguish is an affect, but he considers it not to be a symptom. To the extent that it configures anguish as an affect, it characterizes it aimlessly, completely adrift, because it is never repressed. It is this characteristic of it that makes it so unsettling, as it is not tied to the network of signifiers that is impossible to represent. In this way, the psychoanalytic clinic in the health institution considers the difference between illness inscribed in the body and illness as an experience. In this aspect, the psychoanalyst will seek to provide the transition from the event itself to an experience, enabling the construction of subjectivation, elevating such illness to the position of experience producing unique knowledge. Since we are part of the hospital institution, it is important to think about the time of each subject, since the temporality of the hospital ignores its own temporality. Lacan presents us with the problematic of logic regarding time, discussing the constitution of three instances, namely: the moment of seeing, the time of understanding, the moment of concluding. We can associate these three concepts with the experience of becoming ill with cancer. Being the moment of seeing, the oncological diagnosis and despair emerged in the face of the certainty of one's own death, confronting the patient with the reality of human finitude. When moving to the time of understanding, with the establishment of transference, the subject reaches the process of psychic elaboration. And finally, the psychic work ends with the moment of concluding what you asked about. And as the subject is faced with such subjective experiences, he is confronted with the transience of his own life. The research method used was the clinical case study, carried out in a hospital institution in Belém do Pará, a reference in oncological treatment. The general objective was to understand psychoanalytic clinical practice in the hospital context, specifically the psychic elaboration based on the experience of anguish in cancer patients. The specific objectives included the investigation of the conception of anguish by Freud, Lacan and their commentators, the exploration of the relationship between anguish and cancer, and the identification of the process of elaboration of psychological suffering in cancer patients.